The Dual Role of Natural Organic Matter in the Degradation of Organic Pollutants by Persulfate-Based Advanced Oxidation Processes: A Mini-Review - Dan Luo; Hansen Lin; Xingzhen Li; Yu Wang; Long Ye; Yuebang Mai; Peihao Wu; Zhuobiao Ni; Qingqi Lin; Rongliang Qiu (Toxics)
Persulfate-based advanced oxidation processes (PS-AOPs) are widely used to degrade significant amounts of organic pollutants (OPs) in water and soil matrices. The effectiveness of these processes is influenced by the presence of natural organic matter (NOM), which is ubiquitous in the environment. However, the mechanisms by which NOM affects the degradation of OPs in PS-AOPs remain poorly documented. This review systematically summarizes the dual effects of NOM in PS-AOPs, including inhibitory and promotional effects. It encompasses the entire process, detailing the interaction between PS and its activators, the fate of reactive oxygen species (ROS), and the transformation of OPs within PS-AOPs. Specifically, the inhibiting mechanisms include the prevention of PS activation, suppression of ROS fate, and conversion of intermediates to their parent compounds. In contrast, the promoting effects involve the enhancement of catalytic effectiveness, contributions to ROS generation, and improved interactions between NOM and OPs. Finally, further studies are required to elucidate the reaction mechanisms of NOM in PS-AOPs and explore the practical applications of PS-AOPs using actual NOM rather than model compounds.